2017
DOI: 10.1088/1361-6528/aa765b
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric effects in boron nitride nanotubes predicted by the atomistic finite element method and molecular mechanics

Abstract: We calculate the tensile and shear moduli of a series of boron nitride nanotubes and their piezoelectric response to applied loads. We compare in detail results from a simple molecular mechanics (MM) potential, the universal force field, with those from the atomistic finite element method (AFEM) using both Euler-Bernoulli and Timoshenko beam formulations. The MM energy minimisations are much more successful than those using the AFEM, and we analyse the failure of the latter approach both qualitatively and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[ 6 ] Of particular interest are BNNTs’ piezoelectric properties, [ 7 ] arising from polarization due to the electronegativity difference between boron and nitrogen atoms, which is predicted to result in the generation of a coupled electric dipole in response to deformation. [ 8 ] With the advent of techniques to produce large volumes of BNNTs such as the high temperature pressure (HTP) method, [ 9,10 ] interest has shifted to production of ensembles of BNNTs which translate the nanoscale properties of BNNTs to macroscale systems.…”
Section: Figurementioning
confidence: 99%
“…[ 6 ] Of particular interest are BNNTs’ piezoelectric properties, [ 7 ] arising from polarization due to the electronegativity difference between boron and nitrogen atoms, which is predicted to result in the generation of a coupled electric dipole in response to deformation. [ 8 ] With the advent of techniques to produce large volumes of BNNTs such as the high temperature pressure (HTP) method, [ 9,10 ] interest has shifted to production of ensembles of BNNTs which translate the nanoscale properties of BNNTs to macroscale systems.…”
Section: Figurementioning
confidence: 99%
“…The nature of the piezoelectricity of single-walled BNNTs has been demonstrated experimentally, although it is not completely understood (Tiano et al 2014). Numerical and molecular mechanics simulations, however, have been able to approximate the resultant dipolar vector in single-walled nanotubes after an applied stress (Tolladay et al 2017; Tiano et al 2014), while others have found theoretical piezoelectric response values higher than those of piezoelectric polymers (Dai et al 2009). Likewise, multi-walled BNNTs have also shown experimental signs of piezoelectricity (Bai et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…[52,64] The nature of the piezoelectricity of single-walled BNNTs has been demonstrated experimentally, although it is not completely understood. [52] Numerical and molecular mechanics simulations, however, have been able to approximate the resultant dipolar vector in single-walled nanotubes after an applied stress, [52,65] while others have found theoretical piezoelectric response values higher than those of piezoelectric polymers. [66] Likewise, multiwalled BNNTs have also shown experimental signs of piezoelectricity.…”
Section: Characterization Of Bnntsmentioning
confidence: 99%